Tinjauan Pustaka tentang Peran Multimedia Pembelajaran dalam Mendukung Hasil Belajar Kognitif dan Konseling Anak Usia Dini dari Perspektif Pendidikan Islam: Literature Review on the Role of Multimedia Learning in Supporting Early Childhood Cognitive Learning Outcomes and Counseling from an Islamic Education Perspective - Irawati Rahayu; Siti Aliyah; Deni Darmawan (Program Studi Bimbingan Konseling Islam, Fakultas Tarbiyah Dan Ilmu Keguruan, Institut Ummul Quro Al-Islami Bogor, 2023)
This literature review discusses the impact of using multimedia learning on cognitive learning outcomes of early childhood and the role of counseling in supporting holistic development of children. Learning is understood as a process of behavioral change that is influenced by the environment and leads to positive development, especially in the cognitive domain related to brain function such as memory and intellectual ability. Multimedia learning that combines text, sound, images, animation, and video is considered very effective for early childhood because it is in accordance with their developmental characteristics. In addition to cognitive aspects, counseling plays an important role in providing emotional and social support to children, helping to overcome learning barriers, and forming positive character and attitudes. Studies show that multimedia such as videos and educational games can increase motivation, engagement, and learning effectiveness. The right combination of multimedia and counseling can optimize cognitive development as well as psychosocial aspects of children. In conclusion, the integration of multimedia learning with a counseling approach has been proven effective in improving critical thinking skills, problem solving, and psychological well-being of early childhood. These findings are an important basis for the development of multimedia teaching materials and appropriate counseling strategies, especially from an Islamic education perspective, to support children's growth and development as a whole.